Edukasi Program Posyandu dimasa Pandemi Covid-19 sebagai Upaya Membentuk Persepsi Masyarakat di Wilayah Kerja Posyandu Cempaka Kelurahan Kuin Selatan Kota Banjarmasin - Norfai Norfai; Eddy Rahman; Abdullah Abdullah (Jurnal Abdimas Kesehatan (JAK), 2021)
The purpose of this service activity is to increase public knowledge, especially mothers who have babies or children under five years (balita), about the posyandu program. Before starting counseling, a questionnaire was filled (pretest). Counseling uses power point media with the lecture, discussion and question and answer method, then after being given counseling, the same questionnaire was distributed again to be filled back (posttest), after the knowledge data before and after counseling had been obtained, then the data were analyzed using the Wilcoxon statistical test.Based on the results of community service activities in the work area of the Banjarmasin Kuin Selatan Village Cempaka Posyandu, it means that there is a significant difference in knowledge between before and after counseling using power point media, thus it can be concluded that the method of extension using power point media carried out in the work area of the Banjarmasin Kuin Selatan Village Cempaka Posyandu is able and successful in increasing the knowledge of mothers who have chldren under five years. It is recommended that the local public health service (puskesmas) can provide more intensive guidance and training to posyandu cadres, so that they can assist health workers in educating the public about health in general and information about the importance of posyandu and the activities at the posyandu itself as an effort to participate forming a positive perception of the posyandu